Evaluation of supporting document completeness in outpatient claims to prevent BPJS claim returns at charitas Hospital Palembang - Miliana, Elta; Pamungkas, Canggih Ajika (Science Midwifery, 2025)
This study examined the completeness of outpatient claim documents and how it affected the return of claims by the national health insurance agency at Charitas Hospital Palembang. Incomplete documents often delay claim verification and lead to financial loss for healthcare providers. The research used a quantitative approach and analyzed 206 outpatient claim files submitted between February and June 2025. Data were collected through observation checklists and structured questionnaires distributed to administrative staff. The findings revealed that most returned claims were caused by missing laboratory or radiology results, incomplete referral documents, and inconsistent medical records. Statistical analysis showed a strong correlation between document completeness and the frequency of returned claims. Factors such as coordination between hospital units, staff competence, and the effectiveness of hospital information systems were found to significantly influence the completeness of claim files. The study concluded that improving internal communication, enhancing staff training, and optimizing electronic record systems can reduce the risk of claim rejection and improve financial sustainability.